LEXICAL DENSITY ANALYSIS OF READING TEXT IN BAHASA INGGRIS TEXTBOOK FOR GRADE XI SMAN 2 TEBING TINGGI - Dibasari Putri and Yeni Arlita (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2017)
This study deals with the lexical density of reading text of English textbook for senior high school. It was aimed to find out lexical density level in the reading text,how is the lexical density distributed across the texts and then why is the lexical density used in the textbook. This study was conducted by using qualitative research.The data of study were the 8 texts that classified by 4 genres in the Bahasa Inggris textbook for grade XI SMAN 2 Tebing Tingi. The data were analyzed by using Eggins (2004) theory. The result of this study: 1) The LD level of text was equal based on Eggins theory. 2) The distribution of lexical density in reading text in Bahasa Inggris textbook as follows: Text 1 entitle “ How to Make Orange Juice” was 0.37. Text 2 entitle “ How to plant Jasmine “ was 0.46. Text 3 entitle “ How to Make Cheese Toast” was 0.37. Text 4 entitle “ How to Make a Pizza” was 0.44. Text 5 entitle “ Earthquakes “ was 0.46. Text 6 entitle “ The Last “ was 0.32. Text 7 entitle "Life and Times of Ki Hajar Dewantara” was 0.38. Text 8 entitle“ Global Warming” was 0.47. 3) Although the reading texts in the bahasa inggris textbook had different genre in each texts but it didn’t influence lexical density of the text because the influencing of the high and low lexical density in the texts were the three points of experiential mode namely action, reconstraction and generalization.